Your name is a song - Thompkins-Bigelow, Jamilah (Innovation Press, 2020)
Saddened by her classmates' and teacher's mispronunciations of her name, a girl is empowered by her discovery that names are like songs when she and her mom celebrate the musicality of African, Asian, Black-American, Latinx, and Middle Eastern names.